Pharmacological Cardioversion of Atrial Fibrillation In Nepalese Population - Rawat, Bharat; Karki, D.B; Jha, SC; Gurung, Jesson; Acharya, Subhash; Sodhi, HS; Pandey, M; Dhonju, Sudarshan; Pande, Rajib (Nepalese Heart Journal, 2004)
Intravenous Procainamide and Oral Flecainide are often used for cardioversion of Paroxysmal Atrial Fibrillation (AF). Hypertensive patients may have problems of proarrythmias with these agents and Intravenous Amiodarone may be an effective safer alternative. The utility of Intravenous Amiodarone in such group of patients in the Himalayan kingdom of Nepal has never been assessed.